Succession of Actinomycetes During Composting Proccess of Dairy-Farm Waste Investigated by Culture-Dependent and Independent Approaches - Mukhlissul Faatih; Jaka Widada; N. Ngadiman (Indonesian Journal of Biotechnology, 2008)
Mesophilic, thermophilic, and maturation phases were recognized in composting proccess. Temperature changes influence the microbial communities in compost within composting proccess. Actinomycetes account for a larger part of compost microbial population. The aim of this research was to study succession of actinomycetes community during composting of dairy-farm waste investigated by culture-dependent and independent approaches. In culture-independent method, the succession of actinomycetes community was analyzed by nestedpolymerase chain reaction of ribosomal intergenic spacer (nested-PCR RISA) using spesific primer F243 and primer R23S followed by a second PCR using primers F968 and R23S. In culture-dependent method actinomycetes from compost were isolated on selective media, starch-nitrate medium and humic-acid + vitamins medium. DNA of actinomycetes was extracted and amplified by repetitive sequence-based PCR (rep-PCR) using primer BOXA1R. The banding patterns were used to generate dendrograms by UPGMA clustering with NTSYS program. Microcosm containing sterile rice-straw and water which is inoculated with each actinomycetes isolates was used for examining the ability of each isolate in rice-straw degradation. The experiment results showed that succession of both bacteria and actinomycetes was occured within composting proccess of dairy-farm waste. Analysed by culture-independent method revealed that the highest community of compost’s bacteria was on mesophilic, thermophilic, and maturation phases, respectively. Whereas PCR-nested RISA resulted the highest population of actinomycetes was on thermophilic, maturation, and mesophilic phases, respectively. By culture-dependent method was obtained 29 actinomycetes isolates from mesophilic phase, 23 isolates from thermophilic phase, and 19 isolates from maturation phase. Genetic diversity analysis of the obtained isolates showed the presence of phylogenetic grouping on each phase of composting proccess. This result illustrated the occurance of succession of actinomycetes community in compost. The ability of each isolates in rice-straw degradation was different, and SnT9 isolate was found to be a promising rice-straw degrader. Keywords: succession, actinomycetes, composting, nested-PCR RISA, rep-PCR